EFEKTIVITAS PELAKSANAAN KERJA SAMA DAERAH PEMERINTAH KOTA SURABAYA DITINJAU DARI PERMENDAGRI NOMOR 22 TAHUN 2020 TENTANG TATA CARA KERJA SAMA DAERAH DENGAN DAERAH LAIN DAN KERJA SAMA DAERAH DENGAN PIHAK KETIGA - Fina Rohmatika; Ida Wahyuliana (ADISAM PUBLISHER, 2025)
The objective to be achieved in this writing is to find out how the effectiveness of regional cooperation in the scope of the City of Surabaya runs as it should in accordance with the laws and characteristics that live in society, so that it can be said to provide benefits to the surrounding environment and related parties, in the approach used with the method through literature studies of research meeting results and discussion of conditions in the field of legal studies and inseparable from its controversy as an independent and distinctive discipline